Ferro sells North American polymer additives assets to HIG Capital. Issue 2 (February 2015) - Unknown
Abstract : Ferro Corp has completed the sale of its North American polymer additives business to Polymer Additives, Inc, a wholly owned portfolio company of private equity firm H.I.G. Capital, LLC (HIG). Subject to customary working capital and other adjustments, the purchase price is approximately US154 million in cash.